Current scenario on reproductive management and performances of dairy cows in Manikganj district (Annals of Bangladesh Agriculture, 2023)
The aim of the study was to evaluate reproductive management and performance of dairy cows in Manikganj district. A total of 400 cows with varying genetics, including native (N), Sahiwal or Red Sindhi cross with native cows (S or RS×N), and Holstein-Friesian cross (HFC), were randomly selected from 60 farms, between February to November 2022. Various practices linked to reproductive management and parameters associated with reproductive performance, such as calving to first service interval (CFSI), calving to conception interval (CCI), number of services per conception (NSC), and calving interval (CI), along with data on health problems related issues, were collected using a predetermined questionnaire by interviewing farmers and personal observations. Results reveal that visual observation method (100%) was used for estrus detection and 91.67% farmers observed their cows several times in a day. The majority of farmers (78.3%) followed artificial insemination (AI) to conceive their cows. Only 43.3% farmers checked cow’s pregnancy routinely at 90-120 days after breeding by rectal palpation. Additionally, 26.7% farmers maintained dry period of their milch cows, whereas, 73.3% were not interested. Most of the farmers (75.0%) provided vitamin-mineral supplements during gestation period. However, only 30.0% farmers maintained hygienic condition during puerperium period.  The average reproductive performances were CFSI (111.9 ± 18.0, 110.8 ± 21.9 and 106.4 ± 22.1 days), CCI (124.8 ± 20.0, 125.9 ± 21.8 and 121.7 ± 21.3 days), NSC (1.6 ± 0.5, 1.7 ± 0.6 and 1.8 ± 0.6) and CI (409.4 ± 21.4, 412.4 ± 21.8 and 408.3 ± 21.0 days) in N, S or RS×N and HFC cows, respectively (p>0.05). The overall prevalence of reproductive problems was 29.5 % and this rate was 46.0, 33.3 and 27.1% in N, S or RS×N and HFC cows, respectively. Therefore, reproductive management practices were good in majority of farms, but need to improve and performance of cows managed, is acceptable and mostly fall within the reproductive goals for sustainable production and farm income. Ann. Bangladesh Agric. 27(2): 129-144